From binder to mixture: experimental programme on permanent deformation behaviour - Elnasri, Mahmoud Masoud Hamza (2015)
Asphalt mixture, the most common road construction material, comprises bitumen, filler, fine and coarse aggregates, and air voids. Traditionally and for simplification, the mixture is treated as a continuous and homogenous material confined in the domain of linear behaviour. The demand for more durable roads, particularly with the progressive growth in traffic volumes and loads, has raised the requirement for improved design methods. Wisely, before the complex adoption of the nonlinear behaviour, understanding the nature of the internal stress-strain relationships at different scales and determining their linearity limits is essentially required taking into consideration the time and temperature dependency.